THE MERARIQ CULTURE OF THE SASAK IN THE PERSPECTIVE OF ISLAMIC SHARIA - Husnul Hotimah; Arif Widodo (Sociology Education, Teaching Training and Education Faculty, Muhammadiyah University of Kupang, 2021)
Indonesia is a country that is rich in unique and interesting cultures and traditions from various parts of the island of Sabang to Merauke which should be proud, preserved and preserved. One of them is the culture that comes from the Sasak tribe in Lombok, West Nusa Tenggara. The Sasak tribe is one of the tribes in Indonesia who live on the island of Lombok using the Sasak language as its regional language. The Sasak tribe has one unique culture that is still practised by its people today, namely the Merariq culture. Merariq culture is one of a series of marriage processes by taking away the beloved bride. However, the merariq culture is considered inappropriate when viewed from Islamic law, which is the religion of the majority of the Sasak people. In Islam, marriage or marriage in terms of its meaning is to gather and unite. Marriage in Islam is an act that is legalized, has the value of worship and is confirmed in the holy book of the Al-Quran. This article aims to explain the contradiction of merariq culture from the perspective of Islamic law. This article uses a literature study research method. The results showed that in this merariq culture not all aspects violate Islamic law, including in merariq culture there is a procession of the marriage contract which is the legal reference for the bride and groom as a halal partner.